Da'wah Strategy for Islamic Religious Extension in Minority Muslim Communities in Janjimartahan Village, Harian District - Lubis, Tri Purnama Sari; Kustiawan, Winda (Golden Ratio of Social Science and Education, 2024)
This study aims to examine how the da'wah strategy carried out by religious extension workers in increasing Islamic religious knowledge in the community as well as what are the supporting and inhibiting factors faced by religious extension workers and how religious extension workers can overcome supporting factors and inhibiting factors that can cause difficulties in achieving goals. The research method used is field research with a qualitative approach, where data is collected through interviews, observations and documentation involving religious extension workers in Janjimartahan Village directly. The results of the research that have been carried out are that in carrying out da'wah, especially in Muslim minority areas, the right da'wah strategy is needed. The da'wah strategy carried out by religious extension workers in the implementation of da'wah in Janjimartahan Village is with an education strategy and a taklim assembly. Then the inhibiting factor in da'wah in Janjimartahan village is that the majority of the community has a middle to lower economy so that people prioritize work. The solution carried out by religious extension workers is that religious extension workers come to the homes of the Muslim community one by one to be taught religious knowledge and recite.